2009
DOI: 10.1007/s11695-009-9843-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Disease in Morbidly Obese Women After Gastric Bypass and Risk Factors Implicated in Bone Loss

Abstract: There is a significant BMD loss at the femoral neck and lumbar spine a year after gastric bypass. Menopausal patients and those with greater lean mass loss are at greater risk and, consequently, should be closely followed up with periodic densitometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 37 publications
5
67
0
5
Order By: Relevance
“…The change in BMD was evident 1 year postsurgery and was associated with the degree of weight reduction [105]. The marked weight loss after long limbbiliopancreatic diversion (BPD-LL) has been associated with decrease in BMD 1 year after surgery [103], RYGB in morbidly obese patients decreases BMC and BMD 1 year postoperatively [106] and, similarly, in a study with follow-up for a year after gastric bypass surgery there was total hip BMD decrease as well as at the lumbar spine [107]. Fewer data are available for the relatively newer sleeve gastrectomy.…”
Section: Effects Of Bariatric Surgery On Bmdmentioning
confidence: 88%
“…The change in BMD was evident 1 year postsurgery and was associated with the degree of weight reduction [105]. The marked weight loss after long limbbiliopancreatic diversion (BPD-LL) has been associated with decrease in BMD 1 year after surgery [103], RYGB in morbidly obese patients decreases BMC and BMD 1 year postoperatively [106] and, similarly, in a study with follow-up for a year after gastric bypass surgery there was total hip BMD decrease as well as at the lumbar spine [107]. Fewer data are available for the relatively newer sleeve gastrectomy.…”
Section: Effects Of Bariatric Surgery On Bmdmentioning
confidence: 88%
“…However, although some studies showed no significant change in lumbar spine BMD after RYGB surgery [52,53,64], several other studies have reported a significant decline in lumbar spine BMD that varied from 3 to 7 % compared with baseline at 9-12 months post-surgery [55,63,65], with an additional 3 % decrement in one of the studies at 3 years post-surgery [63].…”
Section: Effects Of Roux-en-y Gastric Bypass (Rygb) On Bonementioning
confidence: 93%
“…In accordance with previously described studies [52,63], a recent study of 22 women examined 12 months post-RYGB surgery found that their BMD had decreased by an average of 7.26 % in the lumbar spine, by 8.78 % in the femoral neck, and by 8.59 % at total femur, with associated hyperparathyroidism and elevated urinary concentrations of the bone resorption marker urine N-terminal telopeptide (NTx) [65]. This post-operative bone mass loss occurred in spite of a doubling of 25-hydroxy vitamin D intake amongst study patients via monitored use of multivitamin supplement and regular doses of cholecalciferol.…”
Section: Effects Of Roux-en-y Gastric Bypass (Rygb) On Bonementioning
confidence: 99%
See 2 more Smart Citations